Pintura Fresca Vol.18 No.58 - Editor, The (Cultura de Paz, 2013)
Olga Maradiaga Bygocha d´Amalia María Reneé Pérez Rafael Castellón. DOI: http://dx.doi.org/10.5377/cultura.v18i58.1044 Cultura de Paz • Año XVIII • N° 58 • Septiembre - Diciembre 2012